2008
DOI: 10.14411/eje.2008.063
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the quality and size of host aphid species on the biological characteristics of Aphidius colemani (Hymenoptera: Braconidae: Aphidiinae)

Abstract: Abstract.A suitable host provides, at least, the minimum nutritional and physiological conditions for the development of the immature stages of a parasitoid. Host quality may influence the developmental time, mortality rate, longevity and fecundity of parasitoids. This work evaluates the suitability and quality of Aphis gossypii Glover, Brevicoryne brassicae (Linné), Myzus persicae (Sulzer), Rhopalosiphum maidis (Fitch) and Schizaphis graminum (Rondani) as hosts for Aphidius colemani Viereck. Twenty second-ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 27 publications
1
16
0
8
Order By: Relevance
“…In the banker plant system, we found that female barley and store parasitoids were smaller than female pepper parasitoids. Size is often positively correlated with parasitoid fitness, as with host searching efficiency (Visser, ), flight distance (Eijs & Van Alphen, ), and egg number (Sampaio et al , ). Therefore we believe larger parasitoids have higher fitness than smaller ones, and that this behaviour is consistent with optimal foraging.…”
Section: Discussionmentioning
confidence: 99%
“…In the banker plant system, we found that female barley and store parasitoids were smaller than female pepper parasitoids. Size is often positively correlated with parasitoid fitness, as with host searching efficiency (Visser, ), flight distance (Eijs & Van Alphen, ), and egg number (Sampaio et al , ). Therefore we believe larger parasitoids have higher fitness than smaller ones, and that this behaviour is consistent with optimal foraging.…”
Section: Discussionmentioning
confidence: 99%
“…Newly emerged females of each parasitoid species had been paired into a 2.5×8 cm glass tube and fed a single droplet of honey and a droplet of water daily [126]. As the percent parasitism is similar between aphid instars [127], the present studies were conducted on mixed instars, which were exposed to parasitoids (five replicates per treatment in two blocks).…”
Section: Methodsmentioning
confidence: 99%
“…Em sua maioria, os parasitóides avaliam o tamanho do hospedeiro como um indicador de qualidade (Sequeira & Mackauer 1992 (Sequeira & Mackauer 1992, 1994, Sampaio et al 2008. Dessa maneira, embora os dois hospedeiros de maior tamanho tenham apresentado maior qualidade que A. kondoi, não foi encontrada uma relação linear entre a qualidade e o tamanho do hospedeiro para A. ervi.…”
Section: Parâmetros Biológicosunclassified